Controlling w dobie globalizacji - Karwacki, Piotr (Controlling in the time of globalization, 2005)
The paper presents some considerations about implementing the controlling concept in enterprises in the time of globalization. This method could be efficient in different enterprises' spheres especially in the time of in creasing globalization. This article presents the essence, instruments and the role of controller in the time of globalization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (3); 2005; nr 1093, s. 146-156